Association of triglyceride-glucose index and its related parameters with functional disability: evidence from the China Health and Retirement Longitudinal Study - Wei, ZhiHong; Nie, GuanHua; Li, Ji; Zhang, Jiali; Liu, HaoLin; Ma, MinXuan (Frontiers in Aging Neuroscience, 2025)
BackgroundThe triglyceride-glucose (TyG) index, a marker of insulin resistance, is linked to mortality in coronary artery disease, ischemic stroke, and heart failure. However, its association with functional disability remains unclear. This study explored the relationship between the TyG index, its related parameters, and functional disability.MethodsData were obtained from the China Health and Retirement Longitudinal Study (CHARLS). Functional disability was evaluated using the Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) scales. Multivariate logistic regression and restricted cubic spline (RCS) models were used to assess the associations between TyG-related indices and the risk of functional disability. Subgroup analyses stratified by age, sex, smoking, drinking, and diabetes were performed. Additionally, propensity score matching (PSM) was applied to ensure the robustness of the findings.ResultsThe diagnosis rates were 1,510(16.32%) for ADL limited and 2,620(28.32%) for ADL-IADL limited. The TyG-related indices were significantly associated with ADL limited. [TyG index: Full adjusted OR = 1.23, 95%CI: 1.16–1.30, p < 0.001; TyG-BMI index: Full adjusted OR = 1.11, 95%CI: 1.05–1.18, p < 0.001; TyG-WC index: Full adjusted OR = 1.20, 95%CI: 1.13–1.27, p < 0.001; TyG-WHtR index: Full adjusted OR = 1.07, 95%CI: 1.01–1.14, p = 0.025]. The TyG-related indices were significantly associated with ADL-IADL limited. [TyG index: Full adjusted OR = 1.20, 95%CI: 1.14–1.26, p < 0.001; TyG-BMI index: Full adjusted OR = 1.13, 95%CI: 1.08–1.19, p < 0.001; TyG-WC index: Full adjusted OR = 1.14, 95%CI: 1.09–1.20, p < 0.001; TyG-WHtR index: Full adjusted OR = 1.13, 95%CI: 1.07–1.18, p < 0.001].ConclusionOur findings indicated a trend that, TyG-related indices significantly associated with increased risks of ADL limited and ADL-IADL limited populations.